Photocatalytic degradation of palm oil mill secondary effluent (POMSE) using zinc oxide nanoparticles - Zainuri, Nur Zarifah (2020)
Palm oil mill secondary effluent (POMSE) properties still does not achieve the discharged requirement by the department of environment (DOE). Hence, it would be a solution to the POMSE treatment to recover and reuse the photocatalyst as to meet the development of greener and advanced technologies. However, the study on POMSE treatment using photocatalysis process in presence of ZnO-PEG nanoparticles and its physicochemical is still limited. Therefore, this study reports on the comparison of physicochemical properties between the ZnO nanoparticles in presence of the different type of capping agent Commercial ZnO, ZnO-PEG and ZnO-PVP, photocatalysis of POMSE by using ZnO nanoparticles and their potential of their reusability. The physicochemical of the ZnO nanoparticles had been analysed using XRD, FTIR and TEM where the results show that there are no impurities present in the samples and presenting the nature and chemical bonds for ZnO-PEG, besides having less agglomeration and smaller average in size (25-150 nm) compared to Commercial ZnO and ZnO-PVP. ZnO-PEG nanoparticles have a great potential in degradation of POMSE and this is supported with the results evaluated from four potential factors which are (A) different type of photocatalysts, (B) initial pH of the POMSE, (C) loading of ZnO-PEG and (D) concentration ratio of POMSE. It was found that all the four main factors were substantial, with contributions of (A) 73%, (B) 73 %, (C) 84% and (D) 84% respectively, to the POMSE degradation. Accordingly, the most favourable condition for the photocatalysis process of POMSE is under pH 6.5 in presence of ZnO-PEG with 0.5 g/L for the 25% of concentration ratio of POMSE dilution. The calcination methods portrayed the maximum degradation of POMSE colour after second use by 74% colour removal. Besides, the same molecular components and structures for XRD and FTIR were portrayed which indicates the reusability method is performed well.